PENERAPAN EXTREME PROGRAMMING DALAM PENGEMBANGAN SISTEM INFORMASI PENJADWALAN KULIAH JURUSAN AKUNTANSI POLINES - Agus Suwondo; Ahmad Wafa Mansur; Mardinawati (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Scheduling is a routine job that is carried out every semester in the college academic system. There are two schedules that are often found in universities, namely the scheduling of lectures and exams, both theoretical and practical. The scheduling process is a process for implementing events that contain components of courses, lecturers, classes and semesters in time slots that contain time and space components. Many aspects must be considered in order to process optimal class schedules and exams. The problem that occurs at this time is the process of making teaching decrees for lecturers which is automatic from the existing system. Research begins with planning, designing, coding, and testing. With the improvement of the scheduling information system using extreme programming, it is hoped that it can help make teaching decrees in the Polines Accounting department.